Improving security governance through cohesive prevention policies in the European Union - Ionut-Daniel Moldovan (CES Working Papers, 2019)
Security governance plays an extremely important role in achieving basic stability; every geopolitical context wants to maintain and to perpetuate. the security objective must be perceived both as a sine qua non in insuring current needs, as well as a means to ensure well-drafted mitigation plans for future challenges. The multilevel governance framework must continually focus on emerging threat factors, fast-moving changes in the landscape, people's views and behavior and, perhaps most importantly upon the cultural transformations. The purpose of this paper is to assess the importance of preventive policies and, at the same time, to show how they can lead to good governance. Furthermore, we would like to advance the efficiency of a threat assessment guide on behalf of European institutions, whether there is a clear tool kit commonly put into action, and last but not least, if the instruments of cooperation that these institutions have in their portfolio are enough to forge a strong prevention mechanism. As a result, we will eventually try to demonstrate that decisionmakers need to understand the importance of preventive policies and how they can be developed and used to optimize resources and improve development, progress and efficiency, regardless of areas.
Keywords: 330; security governance; prevention policies; risk management